(untitled) (Bangladesh Rice Journal, 2026)
Since the initiation hybrid rice research in 1993 in collaboration with International Rice Research Institute (IRRI), Bangladesh Rice Research Institute (BRRI) has made significant progress in developing and releasing hybrid rice varieties adapted to local agro-ecologies. As of 2024, a total of 255 hybrid rice varieties have been officially registered, including 33 developed domestically. This study synthesizes BRRI’s achievements in hybrid rice breeding, parental line development, and multilocation performance trials. As documented in 2024, BRRI has released eight hybrid rice varieties five for Boro season, two for T. Aman, and one for T. Aus with a 15–20% yield advantage over modern inbred varieties. Notably, BRRI hybrid dhan3 and BRRI hybrid dhan8 exhibit yield potentials exceeding 10.5 t/ha in the Boro season. BRRI has developed over 20 cytoplasmic male sterile (CMS) lines and 40 restorer lines using germplasm from IRRI, China, India, and indigenous sources. Multi-location trials during T. Aman 2022 season revealed that select hybrids outperformed checks by up to 29% in grain yield. These results underscore the suitability of IRRI-derived CMS lines for Bangladesh’s rainfed conditions and highlight BRRI’s capacity to generate heterotic hybrids for both irrigated and rainfed ecosystems. Continued investment in locally adapted parental lines and strategic field testing will be critical to scaling hybrid rice adoption and enhancing national food security. Seed production and distribution are driven primarily by private companies, which supply 90 percent of hybrid seed, while public research institutes focus on nucleus seed production and quality control. In 2022-23, BRRI developed hybrid rice variety produce 22.89 ton hybrid seed through contact grower which was distributed to different organizations. Bangladesh Rice J.28(2): 39-53, 2024